Reproductive biology of Sporobolus phleoides Hack. (Poaceae) an endemic phalophyte grass of Argentina - Richard, Geraldina Alicia (2015)
Sporobolus phleoides is an endemic grass of Argentina considered an important genetic resource for saline environments due to its salinity tolerance. Basic information about its reproductive biology is needed to adequately preserve its genetic variability. Hence, we studied its breeding system through phenology, embryological analysis, and self-pollination versus open-pollination treatments in six populations collected from four provinces of Argentina. The results indicated that S. phleoides is mainly autogamous with a high fertility rate. Cleistogamous and chasmogamous spikelets are isomorphic and occur simultaneously on the inflorescence, with higher percentages of cleistogamy found in the basal region of the panicle. The average percentage of cleistogamy during the study period was 23 % for all populations evaluated. The development of the embryo sac follows the typical pattern of grasses and indicates normal sexual reproduction. This study provides the basis for programming genotype collections for gene banks and future plans of domestication.